Chest X-ray in right heart disease - Sun, Zhonghua; Liu, D.; Fan, Z. (2018)
© Springer International Publishing AG, part of Springer Nature 2018. Right heart pathology receives less attention from clinicians than left-sided heart disease, and knowledge of the importance of right heart, in particular right ventricle in disease development lags behind that of the left ventricle. In recent years, increasing evidence shows that right heart disease has significant impact on morbidity and mortality, thus highlighting the importance of recognizing right heart disease in clinical practice. Although ultrasound and computed tomography are the most commonly used diagnostic image techniques in the diagnosis of right heart disease, chest radiography still remains the first line technique in many applications. Despite non-specific findings in most of the situations, chest X-ray provides useful information for further diagnostic imaging tests of assessing right heart disease. This chapter provides an overview of applications of chest X-ray in the diagnosis of various right heart diseases.